VBA (Visual Basic for Applications) Based Learning Media Development in Accounting Practice Learning - Ulfa, Agfia Fauziatul; Laily, Nujmatul (Universitas Negeri Malang, 2023)
This research aims to produce learning media products based on Excel VBA (Visual Basic for Applications) in accounting practice learning. This research used the R&D method with the ADDIE model, namely: Analyze, Design, Develop, Implement, and Evaluate. The subjects in this research were Grade XI Financial and Institutional Accounting students at SMK Negeri 2 Kediri. The results showed that the Excel VBA-based learning media showed the media’s feasibility with validation test results by media expert of 100% and material expert of 90.87% and feasible category. In addition, the results of validation test on field practitioners (teachers) and students showed practicality and feasibility of the application of 98.61% and 93.25% respectively for accounting practice learning in Accounting Vocational Schools. Therefore, the presence of Excel VBA application as a learning medium developed is very effective and suitable for use in Accounting Vocational Schools.